Martin's Big words : the life of Martin Luther King, Jr. - Rappaport, Doreen (Jump at the Sun/Hyperion Books for Children, 2001)
A brief biographical sketch of Martin Luther King, Jr., one of the greatest figures in the American civil rights movement.